The defense and signaling role of NADPH oxidases in eukaryotic cells : Review - Breitenbach, Michael; Rinnerthaler, Mark; Weber, Manuela; Breitenbach-Koller, Hannelore; Karl, Thomas; Cullen, Paul; Basu, Sukaniya; Haskova, Dana; Hasek, Jiri (Wiener medizinische Wochenschrift (1946), 2018)
This short review article summarizes what is known clinically and biochemically about the seven human NADPH oxidases. Emphasis is put on the connection between mutations in the catalytic and regulatory subunits of Nox2, the phagocyte defense enzyme, with syndromes like chronic granulomatous disease, as well as a number of chronic inflammatory diseases. These arise paradoxically from a lack of reactive oxygen species production needed as second messengers for immune regulation. Both Nox2 and the six other human NADPH oxidases display signaling functions in addition to the functions of these enzymes in specialized biochemical reactions, for instance, synthesis of the hormone thyroxine. NADPH oxidases are also needed by Saccharomyces cerevisiae cells for the regulation of the actin cytoskeleton in times of stress or developmental changes, such as pseudohyphae formation. The article shows that in certain cancer cells Nox4 is also involved in the re-structuring of the actin cytoskeleton, which is required for cell mobility and therefore for metastasis.
Keywords: NADPH-oxidasa 2; NADPH Oxidase 2; NADPH-oxidasy; lidé; Eukaryotic Cells; Reactive oxygen species; Saccharomyces cerevisiae; NADPH Oxidases; eukaryotické buňky; Nox enzymes; reaktivní formy kyslíku; Humans; Chronic granulomatous disease; NADPH Oxidase 4; NADPH-oxidasa 4; Actin cytoskeleton; Reactive Oxygen Species